1988
DOI: 10.1111/j.1745-6584.1988.tb00398.x
|View full text |Cite
|
Sign up to set email alerts
|

A Collection Manifold for Multilevel Ground‐water Sampling Devices

Abstract: Abstract. A sampling manifold has been developed that allows the rapid collection of ground water from multilevel samplers during tracer tests. Its reliability was proven in an experiment lasting 51 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1990
1990
2003
2003

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Special drilling and sampling methods were developed to minimize disturbance of the aquifer during the emplacement of instrumentation [3], Groundwater was re-circulated between two boreholes 3.41 m apart and the tracers were released in a third "on-line" borehole 0.94 m from the recharge well ( Figure 1). The movement of radiotracers was monitored by removing groundwater from three multi-level sampler installations, using a vacuum extraction system [4], In addition, tracer migration was monitored by gamma probes connected to a multi-channel analyser and which, under computer control, ranged vertically in three blank tubes inserted into the aquifer.…”
Section: Construction and Characterisation Of The Test Arraymentioning
confidence: 99%
See 1 more Smart Citation
“…Special drilling and sampling methods were developed to minimize disturbance of the aquifer during the emplacement of instrumentation [3], Groundwater was re-circulated between two boreholes 3.41 m apart and the tracers were released in a third "on-line" borehole 0.94 m from the recharge well ( Figure 1). The movement of radiotracers was monitored by removing groundwater from three multi-level sampler installations, using a vacuum extraction system [4], In addition, tracer migration was monitored by gamma probes connected to a multi-channel analyser and which, under computer control, ranged vertically in three blank tubes inserted into the aquifer.…”
Section: Construction and Characterisation Of The Test Arraymentioning
confidence: 99%
“…Batch sorption tests showed that acetate had no effect on the sorption of Co but the strong ligand EDTA reduced the distribution ratio. Supporting speciation modelling using PHREEQE showed that EDTA concentrations in excess of 3 mg/1 would be needed to complex 90% of Co added at 1.34 χ 10~1 0 M. 4. When a complex of cobalt-EDTA passed through a repacked sand column it was slightly retarded with a retardation factor of 1.1 and underwent some attenuation.…”
Section: Overall Conclusionmentioning
confidence: 99%
“…Instruments can be equipped Johnson (1982) ,'rodc,'m also be with automatic data collection systems. Data loggers adapted for ground water ,,;ampling (Hitchman, 1988). are commercially available for each type of instrument.…”
Section: Frequencymentioning
confidence: 99%
“…Groundwater samples were collected using a peristaltic pump on a 2 to 3 week schedule. Initially, ports were sampled simultaneously using a vacuum distribution manifold and filter flasks for each sampling port (Hitchman, 1988). However, due to the turbidity of groundwater samples, dissolved 02 measurements were made using a dissolved 02 meter with a polarographic probe.…”
Section: Methodsmentioning
confidence: 99%